A Cross-sectional Survey on the Knowledge and Attitudes towards Zika Virus and its Prevention among Residents of Selangor, Malaysia - Arief, Mohammad; Hassali, Mohamed Azmi Ahmad; Saleem, Fahad; Khan, Muhammad Umair; Ahmad, Akram; Bhagavathulha, Akshaya Srikanth; Jamshed, Shazia Qasim (Journal of Pharmacy Practice and Community Medicine)
Objective: The objectives of this study were to evaluate the knowledge and attitudes towards ZIKV and its prevention among residents of Selangor, Malaysia. Methods: A pre-tested, self administered, cross-sectional survey involving 400 participants was conducted from January to February 2016 in Selangor, a most populated state of Malaysia. Participants were selected using a purposive sampling approach. Descriptive and inferential statistical tests were applied to analyze the data. Results: Of 400 surveys included in the final analysis, 286 (71.5%) respondents showed good knowledge towards ZIKV. The mean knowledge score of the participants was 10.94 ± 3.89. A total of 298 (74.5%) respondents showed a positive attitude towards ZIKV and its prevention. The mean attitude score of the participants was 7.10 ± 2.80 (based on 10 questions). One-third of participants (n=132, 33%) did not consider the need of any protective measure if the male partner is suspected of having ZIKV. A large proportion of respondents (n=190, 47.5%) did not consider Malaysia at risk of ZIKV. Participants’ main source of information about ZIKV was the internet. Conclusion: The findings of this study highlighted important gaps in the knowledge and attitudes of Selangor residents towards ZIKV and its prevention. There is a need for developing customized interventions to bridge these gaps as it is critical to prevent the spread of ZIKV in Malaysia.
Keywords: Knowledge; Attitude; Zika virus; Infection; Public; Malaysia